2017
DOI: 10.1182/blood-2016-07-725754
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF-induced sympathetic tone provokes fever and primes antimobilizing functions of neutrophils via PGE2

Abstract: Granulocyte colony-stimulating factor (G-CSF) is widely used for peripheral blood stem/progenitor mobilization. G-CSF causes low-grade fever that is ameliorated by nonsteroidal anti-inflammatory drugs (NSAIDs), suggesting the activation of arachidonic acid (AA) cascade. How G-CSF regulated this reaction was assessed. G-CSF treatment in mice resulted in fever, which was canceled in prostaglandin E synthase (mPGES-1)-deficient mice. Mobilization efficiency was twice as high in chimeric mice lacking mPGES-1, spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 40 publications
2
52
0
Order By: Relevance
“…Surprisingly, studies in murine models of myocardial injury have shown that adrenergic signalling directly on leucocytes modulates inflammation. Although different forms of β‐adrenergic receptors are expressed on neutrophils, β1‐AR was found to be critical in early stages of myocardial injury: an antagonist for this receptor impaired the migration of neutrophils towards chemotactic stimuli in vitro and hematopoietic‐specific deficiency in the receptor protected from acute injury during the early stages of infarction . Interestingly, inhibition of this receptor leads to aberrant morphology of intravascular neutrophils and reduced motility, similar to that found upon disruption of platelet‐neutrophil interactions .…”
Section: Adrenergic Signalling During Vascular Inflammationmentioning
confidence: 91%
“…Surprisingly, studies in murine models of myocardial injury have shown that adrenergic signalling directly on leucocytes modulates inflammation. Although different forms of β‐adrenergic receptors are expressed on neutrophils, β1‐AR was found to be critical in early stages of myocardial injury: an antagonist for this receptor impaired the migration of neutrophils towards chemotactic stimuli in vitro and hematopoietic‐specific deficiency in the receptor protected from acute injury during the early stages of infarction . Interestingly, inhibition of this receptor leads to aberrant morphology of intravascular neutrophils and reduced motility, similar to that found upon disruption of platelet‐neutrophil interactions .…”
Section: Adrenergic Signalling During Vascular Inflammationmentioning
confidence: 91%
“…At end-product of the arachidonic acid pathway, PGE2 can reportedly expand HSCs in vitro and in vivo [45,46]. Moreover, neutrophil-derived PGE2 inhibits G-CSF-mediated HSPC mobilization [47]. These observations indicate that the relationship of FA-derived lipid molecules to HSC dynamics should be further investigated.…”
Section: Adipocytes Fatty Acid Metabolism and Hematopoiesismentioning
confidence: 98%
“…In particular, a subset of granulocytes expressing the histidine-decarboxylase and histamine was shown to support the quiescence of myeloid-biased HSCs [ 117 ]. Moreover, BM neutrophils can secrete prostaglandin E 2 which promotes the retention of HSC in the BM through the production of osteopontin by the preosteoblasts [ 118 ].…”
Section: Neutrophil Heterogeneitymentioning
confidence: 99%